Implementation of Modified Learning of Ball Relay Game on Children's Physical Fitness at SLB - A - Aditya, Muhamad Rizki; Rahma, Shili Tsaqilla; Maylani, Putri Intan; Moelyono, Andross Metta; Astuti, Tiara Nuarasyifa (Journal of Sport Education, Coaching, and Health (JOCCA), 2024)
This study aims to determine whether there is an influence between game modifications on improving the physical fitness of students at SLB Tunanetra. This study is a descriptive qualitative type that will explain the research questions. The data collection technique used in this study was carried out using observation and interviews with students and teachers at SLB-C Cimalaka Sumedang and also concluding previous articles and journals. The results that can be presented in this study are the indirect influence of game modifications on physical fitness.